STRATEGI GURU DALAM MENINGKATKAN MOTIVASI MENGHAFAL AL-QUR’AN SANTRI DI MI AL-AWWAL PALEMBANG - Sulis dia wati; Tutut Handayani; Agra Agra Saputra; Aquami Aquami; Ines Jadidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Effective Qur’an memorization learning requires teachers’ ability to manage the process in a planned and systematic way so that students can be actively involved, motivated, and consistent in maintaining and adding memorization. This study aims to describe teachers’ strategies in increasing students’ motivation to memorize the Qur’an at MI Al-Awwal Palembang and to identify supporting and inhibiting factors that influence the success of the tahfidz program. The research employed a qualitative approach with data collected through observation, interviews, and documentation involving fifth-grade students. The findings show that teachers applied strategies such as providing rewards, direct motivation, scheduled muraja’ah, personal guidance, and varied teaching methods to maintain students’ focus. Supporting factors include students’ intrinsic motivation that views memorization as a spiritual need, parental involvement in monitoring memorization at home, and a religious school environment. Inhibiting factors consist of limited time, student absenteeism, and excessive use of gadgets, although digital devices can also serve as supportive media through murottal or educational applications when properly supervised. The conclusion emphasizes that synergy among teachers, students, parents, and the school creates a positive learning atmosphere, enhances discipline, and sustains students’ motivation, making the tahfidz process more directed, efficient, and continuous. This research is expected to serve as a reference for future studies with broader scope to examine teaching strategies in improving students’ motivation and the quality of Qur’an memorization